The complete conversations with God : an uncommon dialogue - Walsch, Neale Donald (London, United Kingdom : Hodder and Stoughton, 1995)
Neal Donald Walsch was experiencing a low period in his life when he decided to write a letter to God, venting his frustrations. What he did not expect was a response. As he finished his letter, he was moved to continue writing and out came extraordinary answers to his questions. This work presents the answers that Walsch received, helping him to change himself, his life and the way he viewed other beings.
Includes index.
Keywords: GOD